Bone turnover markers response to aerobic versus resistance exercise among postmenopausal Saudi women - Abd El-Kader, Shehab Mahmoud; Neveen Refaey; Amany Gomaa Atiaa; Qawagzah, Subhi Mustafa (J Med Rehab Sci, 2025)
Background: Menopause is characterized with low bone turnover biomarkers (BTMs) with faster reduction of bone mass and high fracture risk. Osteoporosis is considered as a major health related problem among Asian postmenopausal women. Physical exercise is an accepted modality in both primary and secondary prevention fracture related to osteoporosis. However, our understanding regarding the best exercise training program to prevent osteoporosis among postmenopausal women is incomplete. Objective: The present study was designed to examine aerobic versus resisted exercise training effects upon postmenopausal Saudi women markers of bone turnover. Material and Methods: One hundred Saudi postmenopausal women, their age ranged from 50-58 years. Participants enrolled in two groups: Group (A) received treadmill aerobic exercises where, group (B) received resistance exercise training for 6 months. Results: There were significant improvement in six-minute walking test and hand grip strength and significant reduction in serum osteoprotegerin (OPG), receptor activator of nuclear factor kappa B ligand (RANKL) and OPG/receptor activator of nuclear factor kappa B ligand (OPG/ RANKL) ratio after training in the both groups with significant differences between the two groups. Conclusion: Six months of resisted exercise is superior to aerobic exercise in modifying bone turnover markers and functional ability among postmenopausal women.